The evolution of Omega-The International Journal of Management Science over the past 40 years: A bibliometric overview. (June 2020) - Wang, Chao; Lim, Ming K; Zhao, Longfeng; Tseng, Ming-Lang; Chien, Chen-Fu; Lev, Benjamin
Highlights: Bibliometric analysis is applied for a retrospective evaluation of Omega . Identify the most productive and influential authors/institutions/countries. Visualize the relationships and structure of Omega with other journals. Reveal the thematic trends in Omega through keyword co-occurrence network and strategic diagrams. Abstract: The aim of this study is to reflect on where Omega-The International Journal of Management Science ( Omega ) comes from and evaluate where Omega currently is in a field that arguably paves the way for the challenging task of identifying future directions and trends. To achieve this goal, this study presents a bibliometric overview of Omega over the past 40 years, from 1979 to 2018. First, this study outlines the basic bibliometric profile of Omega . Second, VOSviewer is employed to visualize the collaborative relationships that Omega has with other journals to show how Omega has linked to them over the past 40 years. Finally, co-occurrences of keywords are analysed and strategic diagrams are built to reveal the thematic trends in Omega . The results show that Omega has substantial influences in the field of operational research and management science (OR&MS), with contributors from all over the world. Omega has strong connections with other leading journals in the fields of OR&MS and engineering. The mainstream research of Omega mainly focuses on production and manufacturing management, mathematical modelling for optimization problems, supply chain management, data envelopment analysis, multicriteria and decision making. Moreover, motor themes, highly developed-and-isolated themes, emerging-or-declining themes, and basic-and-transversal themes are identified. The study provides strong evidence that Omega has been a story of success, and the findings of this study will support decision making for the Omega -related scientific community.